A Comparison Between the Skills-Based Education with a Lecture-Based Education on Female Adolescents’ Knowledge, Attitude and Practice about Health in Puberty: A Randomized Trail Study - Nazarpour, Soheila; Arabi, Zeinab; Simbar, Masoumeh; Keshavarz, Zohreh; Baghestani, Ahmad Reza (Advances in Nursing & Midwifery, 2020)
Abstract Introduction: Skills-based health education is useful in the promotion of health behaviors. Preparing for puberty is essential for adolescents. This study aimed to assess the effects of a skills-based education on girls' knowledge, attitudes, and practice about health in puberty. Methods: This was an experimental study on 80 female school students in Tehran, Iran. Two groups of forty participants were randomly designated as the experimental and control in two different high schools in Tehran. A skills-based education program trained the experimental group, and a routine lecture-based education taught the control group about health in puberty. Data was collected using a questionnaire that assessed the participants' knowledge, attitudes, and practice about health in puberty; before, immediately after, and two months after the education. Results: Knowledge and attitude were significantly improved in the skills-based education group comparing to the Lecture-based group, immediately after (P = 0.002 and P = 0.045, respectively) and two months after the interventions (P < 0.001 and P = 0.034, respectively). Both methods were not effective in improving practice. Conclusions: Skills-based health education is more effective than the routine lecture-based education on improving knowledge and attitudes about puberty in health.